2008
DOI: 10.1111/j.1468-5906.2008.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

The Earnings of American Jewish Men: Human Capital, Denomination, and Religiosity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 14 publications
5
32
0
Order By: Relevance
“…The hypothesis that the effects associated with involvement in religious activities are non linear is supported by the present findings regarding the connection between religious participation and women's vulnerability to IPV, and by Chiswick and Huang's (2007) Under the law that finally passed in 2004, divorce continues to be a difficult and costly endeavor. Emphasizing the goal of family unity, the law requires a one-year separation period before divorce can be filed, followed by a three-year period in which the parties must go through a mandatory mediation process (Blofield and Haas 2005).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The hypothesis that the effects associated with involvement in religious activities are non linear is supported by the present findings regarding the connection between religious participation and women's vulnerability to IPV, and by Chiswick and Huang's (2007) Under the law that finally passed in 2004, divorce continues to be a difficult and costly endeavor. Emphasizing the goal of family unity, the law requires a one-year separation period before divorce can be filed, followed by a three-year period in which the parties must go through a mandatory mediation process (Blofield and Haas 2005).…”
supporting
confidence: 67%
“…A recent study specifies it as a set of dummy variables and thus allows for the possibility of non-linearities (Chiswick and Huang 2007). Examining the effects of religious participation on earnings based on data from the 2000/2001 National Jewish Population Survey, the authors find that individuals who attend religious services weekly have significantly higher earnings than those who attend less frequently or not at all, supporting the hypothesis that some religious involvement has a beneficial effect on labor market outcomes; however, those who attend services more than weekly have lower earnings than those who attend weekly.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to particular questions, the biggest problem is the low response rate regarding income, which is always a sensitive question. Chiswick and Huang's (2008) analysis suggests that the non-response on this topic is biased toward higher-income respondents, as might be expected.…”
Section: The Datamentioning
confidence: 67%
“…Many respondents are reluctant to report what their annual earnings are, not only on the NJPS but on surveys in general. An analysis of the response patterns for the 2000-01 NJPS has shown that the non-response is biased toward higher-income earners, at least among men (Chiswick and Huang, 2008). There is no reason to expect that this pattern differs for women.…”
Section: Occupational Rewardsmentioning
confidence: 99%